ARK 2015: AWI airborne accumulation radar data in Northeast Greenland at the 79 NG (Nioghalvfjerdsbræ) (MABANG project) - Angelika Humbert; Daniel Steinhage; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI Accumulation radar system (ACCU; Janett, M.& Steinhage, D., 2012) during the Arctic season of 2015. The profiles extend across the Northeast Greenland Ice Sheet at the 79 NG (Nioghalvfjerdsbræ). The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.